2015
DOI: 10.1007/s11590-015-0917-0
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of the Lisbon voting rules in the EU Council: a challenge and new world record

Abstract: ABSTRACT. The new voting system of the Council of the European Union cannot be represented as the intersection of six or fewer weighted games, i.e., its dimension is at least 7. This sets a new record for real-world voting bodies. A heuristic combination of different discrete optimization methods yields a representation as the intersection of 13 368 weighted games. Determination of the exact dimension is posed as a challenge to the community. The system's Boolean dimension is proven to be 3.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 13 publications
1
44
0
Order By: Relevance
“…This leads direct enumeration to be the only feasible way of certifying which coalitions are winning and which ones are losing. The computational study by Kurz and Napel (2016) shows that dimension of the Lisbon voting system is at least seven, i.e. a combination of at least seven weighted voting games is needed to obtain the set of winning coalitions under the Lisbon voting system.…”
Section: Winning Coalitions and The Analysis Of Decision Efficiencymentioning
confidence: 99%
“…This leads direct enumeration to be the only feasible way of certifying which coalitions are winning and which ones are losing. The computational study by Kurz and Napel (2016) shows that dimension of the Lisbon voting system is at least seven, i.e. a combination of at least seven weighted voting games is needed to obtain the set of winning coalitions under the Lisbon voting system.…”
Section: Winning Coalitions and The Analysis Of Decision Efficiencymentioning
confidence: 99%
“…Freixas (2004) showed that the dimension of the European Union Council under the Nice rules had dimension 3. In a recent article Kurz and Napel (2015) have found that the revised voting rules of the Council of the European Union (EU Council) mean that a simple game representation of that voting body must have dimension at least 7. This is significantly larger than that of any other known simple game that occurs in the real world.…”
Section: Complete and Hierarchical Simple Gamesmentioning
confidence: 99%
“…To bound the dimension of a game from below we will use the following useful criterion, which is Observation 1 in Kurz and Napel (2015). It is so important that we call it a theorem.…”
Section: Complete and Hierarchical Simple Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many theoretical results and examples about dimension and codimension [11,8,3,7,5,12,6] have been constantly appearing during the last years, as well as, computational complexity results [9,4,1]. We present some results that will be used in Section 2.…”
Section: Introductionmentioning
confidence: 99%